Korelasi Ukuran Batu Ginjal dengan Jumlah Dilakukan ESWL di Rumah Sakit Islam Sultan Agung pada Tahun 2019: Correlation of Kidney Stone Size with the Frequency of ESWL Performed at the Sultan Agung Hospital in 2019 - Alisha Rahma Bilqisthi; Bondan Prasetyo; Romadhoni Romadhoni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Stone size affects the stone free after (Extracorporeal Shock Wave Lithotripsy) ESWL. The larger the stone size is negatively correlated with the stone free. One of the efforts that can be done is to do ESWL again. The purpose of this study was to determine the correlation between kidney stone size and the frequency of ESWL performed in patients with kidney stones. This study used an observational analytic design with a cross sectional retrospective approach with a sample of 68 people obtained by consecutive sampling. Data were collected using secondary data (medical records) and analyzed using the pearson product moment correlation. The results of the pearson product moment correlation test with = 0.05 showed a significant correlation between the size of kidney stones and the number of ESWL performed with value = 0.000 with a value of r = 0,657. The Conclusion of this study is there is a significant correlation between kidney stone size and the frequency of ESWL performed. The larger the size of the kidney stones, the greater the number of ESWL therapy performed.